Laser spectroscopy of indium Rydberg atom bunches by electric field ionization - Vernon, A. R.; Ricketts, C. M.; Billowes, J.; Cocolios, T. E.; Cooper, B. S.; Flanagan, K. T.; Garcia Ruiz, R. F.; Gustafsson, F. P.; Neyens, G.; Perrett, H. A.; Sahoo, B. K.; Wang, Q.; et al. (Scientific reports, 2020)
This work reports on the application of a novel electric field-ionization setup for high-resolution laser spectroscopy measurements on bunched fast atomic beams in a collinear geometry. In combination with multi-step resonant excitation to Rydberg states using pulsed lasers, the field ionization technique demonstrates increased sensitivity for isotope separation and measurement of atomic parameters over previous non-resonant laser ionization methods. The setup was tested at the Collinear Resonance Ionization Spectroscopy experiment at ISOLDE-CERN to perform high-resolution measurements of transitions in the indium atom from the 5s 2 5d 2 D 5 / 2 and 5s 2 5d 2 D 3 / 2 states to 5s 2 n p 2 P and 5s 2 n f 2 F Rydberg states, up to a principal quantum number of n = 72 . The extracted Rydberg level energies were used to re-evaluate the ionization potential of the indium atom to be 46 , 670.107 ( 4 ) cm - 1 . The nuclear magnetic dipole and nuclear electric quadrupole hyperfine structure constants and level isotope shifts of the 5s 2 5d 2 D 5 / 2 and 5s 2 5d 2 D 3 / 2 states were determined for 113 , 115 In. The results are compared to calculations using relativistic coupled-cluster theory. A good agreement is found with the ionization potential and isotope shifts, while disagreement of hyperfine structure constants indicates an increased importance of electron correlations in these excited atomic states. With the aim of further increasing the detection sensitivity for measurements on exotic isotopes, a systematic study of the field-ionization arrangement implemented in the work was performed at the same time and an improved design was simulated and is presented. The improved design offers increased background suppression independent of the distance from field ionization to ion detection.